Propozycja modyfikacji finansowania polskiego systemu rekompensat dla inwestorów giełdowych - Janik, Bogna (Modification of changes in Polish system of compensations for stock exchange investors - a proposal, 2006)
Compensation system for stock exchange investors is an element of security system which is to protect small investors against loss of financial means, as well as financial instruments, in case of declaring bankruptcy. However, the system does not protect investor from the results of his “wrong” decisions, for instance allocation of sources in financial instruments resulting in eg. decrease of their value. The system provides protection from loss of value in case of investment institution declaring insolvency. The limit of protection in Polish compensation system is 22 000 euro and is the minimum specified in Investor Compensation Directive ( ICD). While estimating the amount of protection limit the analysts use the ratio - the amount of compensation to Gross Domestic Product (GDP) per capita. The ratio in Poland is 4.85 and is one of the highest in EU 25 countries. Policy of hoarding means for payments made to persons entitled is an important element of every investor protection system. Financial means, necessary for realizing compensations, come from payments made by investment institutions which are obliged to participate in the system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 156-165